Songs of the humpback whale a novel in five voices - Picoult, Jodi (New York Washington Square Press, 2001)
After a family argument, Jane takes her daughter, Rebecca, and travels across the country to stay with her brother Joley, and Oliver, her oceanographer husband, tries to track her unpredictable path.
Originally published: Boston : Faber and Faber, 1992.
This printing contains a "WSP readers club" guide.
"First Pocket Books trade paperback printing October 2001"--Title page verso.
107374
Keywords: Interpersonal relations -- Fiction; Families -- Fiction; Family life -- Fiction; Domestic fiction; Fiction